POLITICAL CONNECTIONS, CEO DUALITY, AUDIT COMMITTEE INDEPENDENT ON THE COST OF DEBT - Icih Icih; Tuti Sumanih (JASS (Journal of Accounting for Sustainable Society), 2022)
This study aims to determine whether political connections, CEO duality and independent audit committee have an effect on. Debt interest expense this research is a quantitative type of research using secondary data obtained from the Bursa Malaysia web, the population in this study uses the financial service sector in the 2017-2020 period. This research uses multiple linear regression analysis. The results show that political connection have a negative effect on the interest cost of debt with CEO duality having a negative relationship, and independent audit committees are proven to have an effect on the interest cost of debt.